Quantitation of melatonin and n-acetylserotonin in human plasma by nanoflow LC-MS/MS and electrospray LC-MS/MS - Carter, Melissa D.; Wade Calcutt, M.; Malow, Beth A.; Rose, Kristie L.; Hachey, David L. (Journal of mass spectrometry., 2012)
Melatonin (MEL) and its chemical precursor N‐acetylserotonin (NAS) are believed to be potential biomarkers for sleep‐related disorders. Measurement of these compounds, however, has proven to be difficult due to their low circulating levels, especially that of NAS. Few methods offer the sensitivity, specificity and dynamic range needed to monitor MEL and its precursors and metabolites in small blood samples, such as those obtained from pediatric patients. In support of our ongoing study to determine the safety, tolerability and PK dosing strategies for MEL in treating insomnia in children with autism spectrum disorder, two highly sensitive LC‐MS/MS assays were developed for the quantitation of MEL and precursor NAS at pg/mL levels in small volumes of human plasma. A validated electrospray ionization (ESI) method was used to quantitate high levels of MEL in PK studies, and a validated nanospray (nESI) method was developed for quantitation of MEL and NAS at endogenous levels. In both assays, plasma samples were processed by centrifugal membrane dialysis after addition of stable isotopic internal standards, and the components were separated by either conventional LC using a Waters SymmetryShield RP18 column (2.1 × 100 mm, 3.5 µm) or on a polyimide‐coated, fused‐silica capillary self‐packed with 17 cm AquaC18 (3 µm, 125 Å). Quantitation was done using the SRM transitions m/z 233 → 174 and m/z 219 → 160 for MEL and NAS, respectively. The analytical response ratio versus concentration curves were linear for MEL (nanoflow LC: 11.7–1165 pg/mL, LC: 1165–116500 pg/mL) and for NAS (nanoflow LC: 11.0–1095 pg/mL). Copyright © 2012 John Wiley & Sons, Ltd.